Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1093/pubmed/fdx032
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities in maternal pertussis vaccination uptake: a cross-sectional survey of maternity units

Abstract: Pertussis vaccine uptake in pregnant women varies significantly across the country and is affected by ethnicity, deprivation and parity. Variations should be addressed through service delivery models designed to reduce potential inequalities in infant protection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 6 publications
3
20
0
Order By: Relevance
“…This finding is also consistent with previous studies in different international contexts. 12,18,20,45 In England, Byrne et al found that women of Black-British and Black-Afro-Caribbean ethnicity had the lowest maternal pertussis vaccine coverage and reported that deprivation was linked to low maternal vaccine coverage. 17 Black-Afro Caribbean women's vaccine hesitancy might relate to wider feelings of discrimination by the healthcare system associated with ethnicity and socio-economic deprivation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is also consistent with previous studies in different international contexts. 12,18,20,45 In England, Byrne et al found that women of Black-British and Black-Afro-Caribbean ethnicity had the lowest maternal pertussis vaccine coverage and reported that deprivation was linked to low maternal vaccine coverage. 17 Black-Afro Caribbean women's vaccine hesitancy might relate to wider feelings of discrimination by the healthcare system associated with ethnicity and socio-economic deprivation.…”
Section: Discussionmentioning
confidence: 99%
“…12 Maternal vaccine uptake in England varies regionally and has been historically lower in London for both pertussis [13][14][15] and influenza. 16 Deprivation and ethnicity are known predictors of lower maternal pertussis vaccine uptake 17,18 as well as for maternal and child influenza vaccine uptake in England. 19 Previous work conducted by our group in London found low awareness and low maternal pertussis uptake with variation between different ethnicities, with the lowest uptake among Black Afro-Caribbean women 20 (a demographic group including Black African/Caribbean/Black British and women of any other Black background 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to ethnicity, it has also been reported that antenatal vaccination uptake is affected by other factors such as parity and deprivation [ 43 ]. McAuslane et al.…”
Section: Maternal Vaccinationmentioning
confidence: 99%
“…reported that pertussis vaccine uptake was significantly lower in women with parity greater than three (48.1%; 95% CI 37.0–59.4) than in those with parity between one to three (63.0%; 95% CI 58.3–67.5). The same study also found that vaccine uptake was lowest in the most deprived quintile at 52.1% (95% CI 40.2–63.9) when compared with the least deprived quintile at 69.0% (95% CI 60.3–76.5), but this difference was not statistically significant [ 43 ].…”
Section: Maternal Vaccinationmentioning
confidence: 99%
“…17 18 Smaller studies of pertussis and seasonal influenza vaccines have suggested deprivation, ethnicity, maternal age and parity or number of children may be factors in maternal vaccine uptake, but have lacked power to describe these associations fully. [19][20][21][22][23] A better understanding of the social determinants of maternal vaccine uptake could inform targeted public health interventions to improve vaccine uptake and reduce health inequalities.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%